The Sotacarbo gasification pilot platform: Plant overview, recent experimental results and potential future integrations. (5th January 2015) - Pettinau, Alberto; Calì, Gabriele; Loria, Eusebio; Miraglia, Paolo; Ferrara, Francesca
Abstract: Sotacarbo is currently developing several research projects to optimize a coal-to-hydrogen process configuration within the field of hydrogen production through coal gasification for distributed power generation. To achieve this goal, between 2007 and 2008, Sotacarbo built a flexible pilot platform within its Research Centre in the Serbariu former coal mine (Sardinia, Italy), which is still very much into operation. The platform includes a demonstration plant and a pilot air-blown fixed-bed gasifier, the latter equipped with a flexible syngas treatment line for combined power generation and CO2 -free hydrogen production. This paper aims to give a brief description of the whole experimental equipment and to summarize the main results obtained during more than 1700 h of experimental tests in the pilot unit. It is also reported the gasification performance under different operating conditions. A number of different fuels and fuel blends were tested, including South African sub bituminous coal, Sardinian high sulfur coal, lignite from Alaska and wood chips from local forests. Alaska's lignite reached the best gasification performance due to the high reactivity. There is also a quick examination of the syngas cleaning process's main performance. Finally, the very high efficiency of sulfur compounds removal through a zinc oxide-based hot gas desulphurization process suggested to evaluate the possibility to integrate the plant with a fuel cell system for a high efficiency combined heat and power (CHP) generation. The main results of this theoretical assessment, reached through a properly developed simulation model, are also reported in this work. Highlights: The Sotacarbo pilot platform for electrical energy and H2 production is described. Main results from gasification of different coals and biomass are summarized. Lignite presents the best performance, with a syngas production of 73 Nm 3 /h. Clean syngas with less than 1 ppm of H2 S and COS can be directly fed to MCFC stack. Syngas-fed MCFC can allow an electrical efficiency up to 32–33%.